Peran Perawat dalam Melakukan Pengkajian Kebutuhan Pasien Berdasarkan Aspek Biologis, Psikologis, Sosiologis, Spiritual di Ruang Rawat Inap - Ali Syahbana; Dwi Wahyuni; Elfian Zulkarnain (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2019)
An inpatient room is an inpatient place for health services that provides health facilities consisting of doctors, nurses, pharmacists, nutritionists and non-medical personnel to support better patient health. The role of nurses in accordance with laws and regulations is to carry out individual nursing care. Nursing care is mostly done in hospitals. The nursing process consists of the assessment, diagnosis, planning, implementation and evaluation of this matter used by nurses to provide services to patients in the inpatient room. Patients in the inpatient room have biological problems that have been diagnosed according to their conditions and there are other conditions that can affect because human beings are holistic namely biological, psychological, sociological and spiritual. The role of nurses in assessing the needs of patients in the hospital is the first step in determining the diagnosis , planning, implementation, evaluation of nursing. Studies conducted by nurses still tend to be physiological needs but other needs, namely psychological, sociological, spiritual, cannot yet be studied in depth. The purpose of this study was to analyze the role of nurses in conducting a holistic assessment in inpatient diseases in this type of research is a qualitative research case study approach to the method of collecting purposive sampling data collection. Data were collected from the head of the room, the executive nurse and the patient namely 1 key informant, 5 main informants, 2 additional informants. Data collection by in-depth interviews, documents, observations and recorded with a recording device obtained 3 themes, namely carrying out the initial assessment, conducting further studies, psychological, sociological and spiritual assessment only on palliative patients.